National planning in the United States : an annotated bibliography - Wilson, David Eugene, 1939- (Westview special studies in public policy and public systems management., 2018)
This annotated bibliography of more than 2,000 entries, current through 1977, sheds light on the national planning idea as a substantive issue in past, present, and future U.S. public policy; presents a bibliographic structure that suggests new emphases, relationships, and interdisciplinary approaches; and makes more easily accessible to students a